التفكير الإبداعي لربة الأسرة وعلاقته بإدارة الدخل المالي الأسري - النقيب، ريهام كامل السعيد (الجمعية المصرية للاقتصاد المنزلي, 2021)
يهدف البحث الحالي إلى الكشف عن العلاقة بين التفكير الإبداعي لربة الأسرة وإدارة الدخل المالي الأسري، وتكونت عينة البحث من (300) ربة منزل من العاملات وغير العاملات من مستويات اجتماعية واقتصادية مختلفة لديهن أو ليس لديهن أبناء، تم اختيارهن بطريقة صدفية غرضية، وتم استخدام المنهج الوصفي التحليلي، وقامت الباحثة بإعداد استمارة البيانات الأولية للأسرة، استبيان التفكير الإبداعي لربة الأسرة، استبيان إدارة الدخل المالي للأسرة، تم التطبيق الميداني لأدوات البحث في الفترة من 9/2020 حتي 11/2020 ، وأشارت نتائج البحث الحالي إلى وجود علاقة ارتباطية دالة إحصائياً عند مستوى 0.01 بين التفكير الإبداعي لربة الأسرة وإدارة الدخل المالي الأسري ، مما يشير إلى أنه كلما ارتفع التفكير الإبداعي لربة الأسرة كلما كانت إدارتها المالية أفضل لأسرتها.
The current research aims to uncover the relationship between the creative thinking of the head of the family and the management of the family's financial income, and the research sample consisted of (300) housewives who were both working and non-working women of different socio-economic levels with or without children who were chosen in a random and purposeful manner, and the descriptive approach was used Analytical, and the researcher prepared the initial data form for the family, the scale of creative thinking skills of the head of the household, the measure of financial income management for the family, the field application of the research tools was carried out from 9/2020 until 11/2020, and the current research results indicated the existence of a statistically significant correlation relationship at 0.01 level between The creative thinking of the head of the family and the management of the family's financial income, which indicates that the higher the creative thinking of the head of the family, the better her financial management will be for her family.
Keywords: التفكير الإبداعي -- المستوى الاجتماعي -- الدخل المالي -- الدخل الأسري -- الإدارة المالية -- ربة المنزل